Παπαδιαμάντης και Τέννυσον: Μια σύνθετη διακειμενική συνομιλία - Γκότση, Γεωργία; Φαρίνου-Μαλαματάρη, Γεωργία (Σύγκριση/Comparaison/Comparison, 2025)
Papadiamantis and Tennyson: An intricate intertextual relationship This essay investigates the ways in which Alexandros Papadiamandis explores a series of motifs (such as the distant erotic gaze, the unattainable union, the aquatic journey in a state of unconsciousness or death) which are also found in Alfred Tennyson's poetry, particularly in “The Lady of Shalott” and “Lancelot and Elaine”. We argue that, in addition to the more general references to the life and work of the English poet, Papadiamandis became acquainted with Tennyson via his translation (1895–96) of Sarah Grand's novel, The Heavenly Twins. In this New Woman novel, the dialogue with the English poet is frequent and evident. In fact, four short stories by Papadiamandis, which were published after 1895, namely, “A hero's eros” (1897), “Dream on the wave” (1900), “The rosy shores” (1907), and “Dead traveller” (1910), show how the Greek short-story writer assimilates and adapts through his versatile imagination and poetic sensibility in his original work the above motifs.